Financial Report Quality: The Role of Accrual-Based Government Accounting Standards and H.R. Competency - Juniarti, Juniarti; Noersanti, Lina; Gladys, Asthya (Santoso Academy Network, 2023)
This study aims to analyze and obtain empirical evidence about the effect of accrual-based government accounting standards and human resource competencies on the quality of government financial reports. Respondents in this study were employees of the financial division of offices in DKI Jakarta. The financial employee research sample is 100 respondents. The analysis technique uses PLS-SEM with the SmartPLS 3.0 program. The results of this study indicate that the competence of human resources influences the application of P.P. No. 71 of 2010 based on accruals and the quality of financial reports. Meanwhile, the application of accrual-based government accounting standards has no effect on the quality of financial reports. The results of this research can be useful for the government as input and consideration in determining policies, especially related to improving the quality of local government financial reporting information and increasing human resource competence, as well as financial accountability.